(untitled)
Let L = −∆ + V be a Schrödinger operator on R^n , n > 3, where ∆ is the Laplacian on R^n and V ≠ 0 is a nonnegative function satisfying the reverse Hölder's inequality. Let [b, T] be the commutator generated by the Campanato-type function b ∈ Λ^β_L and the Riesz transform associated with Schrödinger operator T = ∇(−∆+V )^12 . In the paper, we establish the boundedness of [b, T] on Lebesgue spaces and Campanato-type spaces. , number=4, journal=Communications in Mathematical Research, year=2021, month=May, pages=289–297